Functionalizing Dendrimers for Targeted Delivery of Bioactive Molecules to Macrophages: A Potential Treatment for Mycobacterium tuberculosis Infection-A Review - Claudia Sanhueza; Daniela Vergara; Catalina Chávez-Aravena; Felipe Gálvez-Jiron; Emigdio Chavez-Angel; Alejandro Castro-Alvarez (MDPI AG, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that replicates inside human alveolar macrophages. This disease causes significant morbidity and mortality throughout the world. According to the World Health Organization 1.4 million people died of this disease in 2021. This indicates that despite the progress of modern medicine, improvements in diagnostics, and the development of drug susceptibility tests, TB remains a global threat to public health. In this sense, host-directed therapy may provide a new approach to the cure of TB, and the expression of miRNAs has been correlated with a change in the concentration of various inflammatory mediators whose concentrations are responsible for the pathophysiology of M. tuberculosis infection. Thus, the administration of miRNAs may help to modulate the immune response of organisms. However, direct administration of miRNAs, without adequate encapsulation, exposes nucleic acids to the activity of cytosolic nucleases, limiting their application. Dendrimers are a family of highly branched molecules with a well-defined architecture and a branched conformation which gives rise to cavities that facilitate physical immobilization, and functional groups that allow chemical interaction with molecules of interest. Additionally, dendrimers can be easily functionalized to target different cells, macrophages among them. In this sense, various studies have proposed the use of different cell receptors as target molecules to aim dendrimers at macrophages and thus release drugs or nucleic acids in the cell of interest. Based on the considerations, the primary objective of this review is to comprehensively explore the potential of functionalized dendrimers as delivery vectors for miRNAs and other therapeutic agents into macrophages. This work aims to provide insights into the use of functionalized dendrimers as an innovative approach for TB treatment, focusing on their ability to target and deliver therapeutic cargo to macrophages.